2002
DOI: 10.1144/gsl.sp.2002.196.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic uplift and denudation of southern Norway: insights from the North Sea Basin

Abstract: The Cenozoic evolution of the North Sea Basin is described, drawing on subsurface data and a series of palaeogeographical maps compiled from a variety of published studies, mainly emphasizing the development of the eastern part of the basin. A model that accounts for the sedimentation history of the North Sea B asin and the topography (including maximum and mean surface elevation) of southern Norway is proposed. The model involves regional plume-related uplift of an initial low-elevation peneplain in early Pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 92 publications
(141 reference statements)
2
22
0
Order By: Relevance
“…Biostratigraphic studies and clinoform geometries reported in previous more localized studies suggest paleo-water depths of 100 -300 m in the deepest part of the basin (e.g. Overeem et al 2001;Huuse 2002;Kuhlmann 2004;King 2016), in agreement with the present study. The lack of slope features on the basal Quaternary surface, as well as limited evidence for extensive facies change between the topset and the slope, is suggestive of the sediment source for the clinoforms being located a significant distance from the clinoform break point (Posamentier & Vail 1988;Mulder & Alexander 2001;Mulder et al 2003).…”
Section: Onset Of the Quaternarysupporting
confidence: 93%
See 3 more Smart Citations
“…Biostratigraphic studies and clinoform geometries reported in previous more localized studies suggest paleo-water depths of 100 -300 m in the deepest part of the basin (e.g. Overeem et al 2001;Huuse 2002;Kuhlmann 2004;King 2016), in agreement with the present study. The lack of slope features on the basal Quaternary surface, as well as limited evidence for extensive facies change between the topset and the slope, is suggestive of the sediment source for the clinoforms being located a significant distance from the clinoform break point (Posamentier & Vail 1988;Mulder & Alexander 2001;Mulder et al 2003).…”
Section: Onset Of the Quaternarysupporting
confidence: 93%
“…The two depocentres could, in fact, indicate completely separate depositional systems: one preserving solely the Scandinavian climate signal from the western coast of Norway, which drained into the northern North Sea, and the other the Northern European signal, or a mixed signal, from eastern Norway draining into the Baltic river system, routed through the southern clinoform set. Rapid northward progradation during this part of the early Quaternary has been noted in the southern North Sea previously, and has been linked with climatic cooling and increased sediment supply owing to glacial activity in the sediment source areas (Overeem et al 2001;Huuse 2002).…”
Section: Onset Of the Quaternarymentioning
confidence: 63%
See 2 more Smart Citations
“…This makes a modest denudation scenario (1-2 km), as proposed by Hall & Bishop (2002), much more plausible than the deep (3 km) scenario of Thomson et al (1999). This is in interesting contrast to the situation on the other side of the North Sea, where there is deep Cenozoic denudation of southern Norway (Huuse, 2002).…”
Section: Discussionmentioning
confidence: 93%